Stroke risk stratification in atrial fibrillation: a review of common risk factors - Oladiran, Oreoluwa (J Community Hosp Intern Med Perspect, 2019)
Atrial Fibrillation (AF) has become a major global health concern being the most common sustained arrhythmia in clinical practice. Risk factors for AF include congestive heart failure, hypertension, increasing age and diabetes. Many of these factors also increase the risk for thromboembolism and ischemic stroke in AF patients. Great efforts have been made from the latter part of the 20(th) century towards developing an ideal stroke risk stratification tool in AF with the aim of reducing the incidence of stroke in AF patients and the limiting unnecessary use of thromboprophylaxis. The thromboembolic risks posed by AF with valvular heart disease are an important subgroup that contributes to a significant proportion of stroke in AF patients globally. We review the evolution of stroke risk stratification and summarize the guidelines for stroke prevention in non-valvular AF as well as AF with valvular heart disease, and the most recent recommendations on stroke prevention in AF patients. Abbreviations: AF: Atrial Fibrillation; ACS: Acute Coronary Syndrome; CAD: Coronary Artery Disease; CCF: Congestive Cardiac Failure; DM: Diabetes Mellitus; EHRA: Evaluated Heartvalves, Rheumatic or Artificial; ICH: Intracranial Hemorrhage; NOACs: Novel Oral Anticoagulants; OAC: Oral Anticoagulants; PAD: Peripheral Arterial Disease ; TIA: Transient Ischemic Attack; VHD: Valvular Heart Disease.